Study of Kampung Chicken Resistance Against Salmonella enteritidis Using TLR4 Gene as Marker - Ulupi , N.; Muladno; Sumantri, C.; Wibawan, I.W.T. (International Journal of Poultry Science, 2014)
Kampung chicken eggs play an important role as substance in ’jamu preparation’ in Indonesia, mostly provided and consumed without cooking. Salmonella free eggs become significant in producing the safe ’jamu preparation’ and such eggs might be produced by chickens which have high resistance to this bacteria. One of excellent markers showing resistance of chicken against Salmonella is an active Toll-like Receptor 4 (TLR4) gene. TLR4 is a phagocytes cell surface receptor that plays a role to recognize lipopolysaccharide of gram negative bacteria including Salmonella enteritidis. It is transcribed by TLR4 gene and conserved in the activation of the non-specific immune system. The aim of the research is to prove resistance of Kampung chicken when was challenged with S. enteritidis, using TLR4 gene as marker. TLR4 gene was genotyped in 50 Kampung chickens with PCR-RFLP. Then all the Kampung chickens were challenged with S. enteritidis (ID50:5×105 CFU/mL). Their expression on resistance against S. enteritidis as well as biological and molecular assays were measured. The genotyping result identified 3 genotypes of TLR4 gene: AA, AG and GG. All parameters including expression of TLR4 gene, concentration of leucocytes, differentiation of leucocytes, macrophages activity and capacity were not significantly different in AG and GG genotypes. There was no S. enteritidis finding in blood and eggs produced by AA, AG and GG chickens. There was found IgY specific to S. enteritidis in eggs yolk with very high concentration (2.94-3.89 mg/mL). The study proved that Kampung chicken resistant to S. enteritidis infection in all condition.